Cereal rye (Secale cereale L.) cover crop improves soil physico-chemical properties with no influence on soybean (Glycine max L.) root growth parameters - Pinnamaneni, Srinivasa R.; Mubvumba, Partson; Anapalli, Saseendran S.; Reddy, Krishna N. (Frontiers in Soil Science, 2022)
Planting winter cover crops (CC) in soybean cropping systems is expected to offer various environmental benefits including soil health and fertility besides enhanced cash crop productivity. In a three-year study (2018–2021) conducted on a Dundee silt loam, we assessed the impact of introducing rye (Secale cereale L.) CC during the winter fallow period on soil organic carbon (SOC), soil organic matter (SOM), soil total nitrogen (STN), bulk density (BD), saturated hydraulic conductivity (Kfs), soil penetration resistance (SPR), and water-stable aggregates (WSA). Three treatments evaluated were: i) no cover crop (NC), ii) winter rye as CC rolled when green and desiccated after soybean planting (GR), and iii) winter rye CC desiccated and rolled before planting soybean (BR) in a randomized complete block design with six replications. The depth of the soil sampling in 2019 was 0-15 and 15-30 cm while 0-10, 10-20 and 20-30 cm depth soil sampling was done in 2020 and 2021. Effects of BR and GR on soybean root growth characteristics (number of roots, root length and root angle) were measured using a CID 600 root scanner. The results showed that CC (both BR and GR) improved SOC by 7 to 12.5%, soil organic matter by 9 to 15%, STN by 13 to 29%, WSA by 26 to 68%, Kfs by 5 to 9% and reduced BD by 8% and SPR by 14 to 18% compared to NC (P<0.05). However, there were no differences between BR and GR treatments. Root characteristics of soybean in the NC, BR and GR treatments were similar. Rye CC fits into the existing soybean production system in the Lower Mississippi Delta with a potential to augment soil-physico chemical properties, thus offering agro-ecosystem services which may not necessarily lead to an impact on soybean root growth traits.